2005
DOI: 10.1159/000087577
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Apolipoprotein E Genotype on Progression of Diabetic Nephropathy

Abstract: Aims: Diabetic nephropathy progresses at a variable rate part of which may be explained by genetic polymorphisms. ApoE polymorphisms are associated with progression of atherosclerosis and because of the similarities between atherosclerosis and glomerulosclerosis, we chose to examine apoE and its role in progression of diabetic nephropathy. Methods: The apoE genotypes of 90 patients with type 2 diabetes and nephropathy who were recruited into a 2-year prospective randomised controlled study comparing intensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 59 publications
3
15
0
Order By: Relevance
“…Several human association studies have shown an association of APOE with renal damage parameters in different groups of patients (Werle et al 1998;Araki et al 2000;Joss et al 2005). Additionally, we found an association between serum APOE levels and albuminuria in the general population (R. Korstanje, unpublished data).…”
supporting
confidence: 68%
“…Several human association studies have shown an association of APOE with renal damage parameters in different groups of patients (Werle et al 1998;Araki et al 2000;Joss et al 2005). Additionally, we found an association between serum APOE levels and albuminuria in the general population (R. Korstanje, unpublished data).…”
supporting
confidence: 68%
“…However, the large number of studies into this issue has failed to reach a definitive conclusion. 1,6,13,15,42 As was the case in our study, several others also claim that carrying e2 allele may increase the risk for DN. For instance, Araki et al showed in their prospective study that the presence of e2 allele increased the risk for DN.…”
Section: Discussionsupporting
confidence: 78%
“…28,[38][39][40][41] APO E also plays a role in central and peripheral nerve regeneration, immunoregulation, cellular growth and differentiation, and recovery of tissue damage. 42 APO E is further claimed to decrease vascular smooth muscle cell proliferation capacity and increase vascular heparan sulfate proteoglycan level. 43 Elevated heparan sulfate proteoglycan levels inhibit mesangial cell proliferation and assist the formation of glomerular basal membrane and main filtration barrier in the interstitium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies 11,12 11,12,14 were recruited into the study of E2E4 versus E3E3 (including 4 comparisons). Twelve reports [11][12][13][14][15][16][17][18][19][20][21][22] were recruited into the study of E3E4 versus E3E3 (including 17 comparisons). Three reports 11,12,14 were recruited into the study of E4E4 versus E3E3 (including 4 comparisons).…”
Section: Study Characteristics For the Relationship Between Apoe Genementioning
confidence: 99%